“It Was Journalism that Abandoned Me”: An Analysis of Journalism in Portugal - Jose Matos (tripleC: Communication, Capitalism & Critique, 2020)
Over the last few decades, journalism in Portugal has undergone a series of changes in both its practice and its conditions. This reconfiguration has been reinforced by the noticeable rise in layoffs and fixed-term contracts, particularly after the implementation of an austerity program over the last few years. This has led many journalists to abandon their job, either voluntarily or otherwise. The present article aims to analyse these trends through the socio-professional trajectories of ex-journalists, seeking to understand what led to the end of their careers, what came after, and what is their current outlook on journalism.